2021
DOI: 10.1590/0100-3984.2020.0016
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of thyroid volume in euthyroid children under 3 years of age

Abstract: Objective: To establish ultrasound reference values for thyroid volumes in children up to 3 years of age, given that ultrasound of the thyroid is an essential examination in the diagnosis of childhood thyroid disease. Materials and Methods: This was a prospective study conducted in an iodine-sufficient city in southeastern Brazil. A total of 100 healthy children underwent clinical evaluation, anthropometric examination, and cervical ultrasound in accordance with conventional protocols. We evaluated characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The volume and hardness of the thyroid gland are pivotal reference indices for dose calculation ( 9 ). Three-dimensional ultrasound imaging technology offers a more precise measurement of thyroid volume compared to conventional ultrasound, with high consistency and repeatability ( 19 ). In contrast to clinical palpation, ultrasound elastography is recognized for quantitatively measuring and reflecting differences in thyroid hardness in GD patients ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…The volume and hardness of the thyroid gland are pivotal reference indices for dose calculation ( 9 ). Three-dimensional ultrasound imaging technology offers a more precise measurement of thyroid volume compared to conventional ultrasound, with high consistency and repeatability ( 19 ). In contrast to clinical palpation, ultrasound elastography is recognized for quantitatively measuring and reflecting differences in thyroid hardness in GD patients ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above, the article authored by Souza et al ( 8 ) , which was published in the previous issue of Radiologia Brasileira , is extremely relevant for the field of pediatric ultrasound in Brazil. The authors determined the mean thyroid volume for each age group, between 5 days and 3 years of age, among children in southeastern Brazil, which is currently considered an iodine-sufficient region, as is the case for most regions of Brazil.…”
mentioning
confidence: 99%
“…The authors determined the mean thyroid volume for each age group, between 5 days and 3 years of age, among children in southeastern Brazil, which is currently considered an iodine-sufficient region, as is the case for most regions of Brazil. Souza et al ( 8 ) reported mean thyroid volumes and established reference values, regardless of sex and height, for two age groups: below 2 months; and between 2 months and 3 years. Although it was a preliminary study, with a small sample, the enormous contribution of the work is that is provides reference values for thyroid volume in euthyroid children, in an age range not previously addressed, within the context of the reality of Brazil.…”
mentioning
confidence: 99%